Insulin signaling and mitochondrial phenotype of skeletal muscle are programmed in utero by maternal diabetes - Klöppel, Eduardo [UNESP] (2024)
Maternal diabetes may influence glucose metabolism in adult offspring, an area with limited research on underlying mechanisms. Our study explored the impact of maternal hyperglycemia during pregnancy on insulin resistance development. Adult female Sprague-Dawley rats from control and diabetic mothers were mated, and their female offspring were monitored for 150 days. The rats were euthanized for blood and muscle samples. Maternal diabetes led to heightened insulin levels, increased HOMA-IR, elevated triglycerides, and a raised TyG index in adult offspring. Muscle samples showed a decreased protein expression of AMPK, PI3K, MAPK, DRP1, and MFF. These changes induced intergenerational metabolic programming in female pups, resulting in insulin resistance, dyslipidemia, and glucose intolerance by day 150. Findings highlight the offspring's adaptation to maternal hyperglycemia, involving insulin resistance, metabolic alterations, the downregulation of insulin signaling sensors, and disturbed mitochondrial morphology. Maintaining maternal glycemic control emerges as crucial in mitigating diabetes-associated disorders in adult offspring.